The Lumber Industry in British Columbia - Jamieson, Stuart (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1971)
The author stresses the point that multi-employer bargaining in a primary or resource-based industry is under some circumstances at least, quite different in character and consequences from its counterpart in other types of industries or other contexts. To illustrate his point, he presents the case of the B.C. Coast Lumber Industry.